The association of dietary flavonoids, magnesium and their interactions with the metabolic syndrome in Chinese adults: a prospective cohort study. Issue 6 (28th September 2021) - Jin, Shanshan; Liu, Junyi; Jia, Yubing; Han, Tianshu; Zhao, Xiujuan; Sun, Changhao; Na, Lixin
Abstract: The aim was to systematically analyse the association of the specific flavonoids, Mg and their interactions from different food sources with the metabolic syndrome (MetS) and its components in a cohort study. A total of 6417 participants aged 20 to 74 years from the Harbin Cohort Study on Diet, Nutrition and Chronic Non-communicable Diseases were included. Multivariate logistic regression analyses, forest plot and restricted cubic spline were performed in the study. After a 5·3-year follow-up, 1283 incident cases of the MetS were reported. Those with a higher total flavonoid intake had a lower risk of the MetS (fourth v . first quartile, relative risk (RR) 0·58; 95 % CI 0·37, 0·93; P = 0·024) and central obesity (RR 0·56; 95 % CI 0·33, 0·95; P = 0·032). Further analysis showed that the specific flavonoids quercetin, kaempferol, isorhamnetin, luteolin, and flavonoids from fruits, potatoes and legumes had the similar associations with risk of the MetS and central obesity ( P < 0·05 for all). A higher intake of total flavonoids, quercetin and luteolin combined with a high level of Mg was more strongly associated with a lower risk of the MetS (RR 0·60; 95 % CI 0·45, 0·81 for total; RR 0·61; 95 % CI 0·45, 0·82 for quercetin; RR 0·52; 95 % CI 0·38, 0·71 for luteolin; all P for interaction < 0·01). Dose–response effects showed an L-shaped curve between the total intake of five flavonoids and the risk of the MetS. A higher flavonoid intake is associated with a lower risk of the MetS and central obesity; their combination with Mg helps to strengthen their negative association with the MetS.